Regional trends in the implementation of artificial intelligence in the system of teacher training in distance learning during martial law - Nataliia Osypova; Olena Kokhanovska; Iryna Zhorova (CTE Workshop Proceedings)
The study is devoted to analysing regional trends in introducing artificial intelligence (AI) into the in-service training system of teachers in the Kherson region of Ukraine in the context of distance learning during martial law. The study's originality lies in identifying specific regional features of the use of AI in the educational process in emergency conditions and developing targeted in-service training programmes adapted to the challenges of wartime. The study aims to identify effective ways to integrate artificial intelligence technologies into the teacher training system and develop their information and digital competence in distance learning. The research methodology included a comprehensive analysis of the regulatory framework, scientific and methodological literature, and a survey of teachers on their readiness for professional development in AI implementation. The study results revealed the main advantages (access to data-based resources, personalisation of the educational process, automation of assessment, creation of interactive learning environments, use of virtual assistants, etc.) and disadvantages (lack of teacher training, ethical issues and technical limitations) of using artificial intelligence in the educational process. Based on the study of AI tools, the content lines of the advanced training programmes "Artificial Intelligence in the Educational Process" and "Neural Networks in Education" of 30 hours (1 ECTS credit) were developed. The study's findings can serve as a basis for developing regional strategies for introducing AI into the educational process, including training, infrastructure development, and cooperation between educational institutions and technology companies.